Contested Eden : California before the Gold Rush - Gutiérrez, Ramón A., 1951-; Orsi, Richard J. (California history sesquicentennial series ;, 1998)
"One of a series of books written to celebrate the 150th anniversary of the admission of California to the Union, emphasizes the natural environment, the history of the Indians, exploration, and social and economic history, rather than the traditional institutional studies of mission and presidio. Takes advantage of the latest research and includes contributions by leading scholars"--Handbook of Latin American Studies, v. 58.